2012
DOI: 10.1017/s0950268812001252
|View full text |Cite
|
Sign up to set email alerts
|

Housing data-based socioeconomic index and risk of invasive pneumococcal disease: an exploratory study

Abstract: SUMMARY We recently developed and validated an index of socioeconomic status (SES) termed HOUSES (HOUsing-based index of SocioEconomic Status) based on real property data. We assessed whether HOUSES overcomes the absence of SES measures in medical records and is associated with risk of invasive pneumococcal disease (IPD) in children. We conducted a population-based case control study of children in Olmsted County, MN diagnosed with IPD (1996–2005). Each case was age- and gender-matched to two controls. HOUSES … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 33 publications
1
30
0
1
Order By: Relevance
“…A high HOUSES score correlates with high SES. Previous research has been used to document the successful application of HOUSES as an effective SES measure in clinical research, [55][56][57][58][59][60][61][62] and HOUSES was recently found to be a useful surrogate for SES to assess risk stratification and hospitalization in adults with multiple chronic conditions. 63 Children with missing address information were excluded from the HOUSES analyses.…”
Section: Sociodemographic Variablesmentioning
confidence: 99%
“…A high HOUSES score correlates with high SES. Previous research has been used to document the successful application of HOUSES as an effective SES measure in clinical research, [55][56][57][58][59][60][61][62] and HOUSES was recently found to be a useful surrogate for SES to assess risk stratification and hospitalization in adults with multiple chronic conditions. 63 Children with missing address information were excluded from the HOUSES analyses.…”
Section: Sociodemographic Variablesmentioning
confidence: 99%
“…Furthermore, these same health outcomes, defined by physician diagnosis or predetermined criteria, were also significantly associated with our original HOUSES index. [7][8][9][10][11][12][13] The performance of modified HOUSES for objective measure-based health outcomes can be expected to be similar to these findings. HOUSES, which is developed based on real property data for US taxation purposes, may not work well in other countries where housing data are not routinely collected or made publicly available in databases, or even in communities within the USA where housing assessments are infrequent or of poor quality.…”
Section: Discussionmentioning
confidence: 82%
“…The HOUSES index predicts health outcomes in adults and children that have previously been identified to be associated with SES (low birth weight, obesity, smoking exposure, asthma control status, pneumococcal diseases, postmyocardial infarction mortality, rheumatoid arthritis (RA) and post-RA mortality). [7][8][9][10][11][12][13] One of the challenges in calculating the original HOUSES index is the need for complex assessor's real property data generated for US taxation purposes. However, these data often does not include key variables of interest such as the number of bedrooms and bathrooms.…”
Section: Introductionmentioning
confidence: 99%
“…Since its original validation, it has been widely used for clinical and epidemiological studies concerning a broad range of health outcomes and behaviors as well as health care delivery in children and adults. 6,[29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] Identifying Areas of Observed and Expected Case Density for AEs…”
Section: Houses As An Individual-level Ses Measurementioning
confidence: 99%